(u-10)*6=48

Simple and best practice solution for (u-10)*6=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (u-10)*6=48 equation:


Simplifying
(u + -10) * 6 = 48

Reorder the terms:
(-10 + u) * 6 = 48

Reorder the terms for easier multiplication:
6(-10 + u) = 48
(-10 * 6 + u * 6) = 48
(-60 + 6u) = 48

Solving
-60 + 6u = 48

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '60' to each side of the equation.
-60 + 60 + 6u = 48 + 60

Combine like terms: -60 + 60 = 0
0 + 6u = 48 + 60
6u = 48 + 60

Combine like terms: 48 + 60 = 108
6u = 108

Divide each side by '6'.
u = 18

Simplifying
u = 18

See similar equations:

| 3*1/3p=114 | | x*log(x)=600000000 | | -2.4n-3+(7.8n+2)= | | Y=-1/2x-12 | | -.5(8x-6)=6x-7 | | 10+6+3x=7*3.5 | | -2m(1+4m)5=-13 | | 2(2l-3+l)=36 | | -(3/x)=0 | | 13/6-1/2 | | 10+4+3x=7*3.5 | | 24.5=2.5-4c | | 7+7y=12x-56 | | -(3/x)0 | | 7v^2+224=-84v | | 10x+20y=360 | | a(n-5)+6=bn | | 6q+1+(q+11)= | | 16+3x=7*3.5 | | 30-45=18 | | 1.25m*7=43.25 | | 2x^2dy=(3xy-y^2)dx | | X+1.5x+0.5x=75 | | sqrt(3x^2+4)-2x=0 | | 4-15=-7 | | -4+3x=20x+9 | | X+1.5x+0.5x= | | l+2l-1+2l+1=30 | | log(x)+log(x-5)=log(5x) | | -4(j+2)=5(j-3) | | c+(3c)+(2.5c)=60 | | (7-x)(x^2+20)= |

Equations solver categories